Study on chloride binding capability of coal gangue based cementitious materials. (10th April 2018) - Yi, Cheng; Ma, Hongqiang; Zhu, Hongguang; Li, Weijian; Xin, Minglang; Liu, Yilei; Guo, Yongdong
Highlights: Coal gangue will become a promising supplementary cementitious materials. The chloride binding isotherm of all specimens can be described by Freundlich equation. The chloride binding capability of slag is stronger than that of coal gangue. The addition of coal gangue can change the chemically and physically bound chloride capability. The chloride binding capability of coal gangue was dependent on the content of alumina, CH and SiO2 . Abstract: The addition of supplementary cementitious materials containing Al2 O3 can improve the chloride binding capability of hardened cement paste to varying degrees, thereby enhancing the durability of reinforced concrete structures. This work was designed to investigate the high-aluminum coal gangue based cementitious materials chloride binding capability, including coal gangue content, coal gangue-slag combined addition and coal gangue calcination temperature. The phase composition and Friedel's salt contents in the specimens were evaluated by XRD and TG-DTG analysis. The results showed that the specimens chloride binding isotherms could be described by Freundlich equation. The coal gangue optimal content was between 20% and 30% and the maximum content was 40%. The chloride binding capability of slag was stronger than that of coal gangue, which promoted the formation of Friedel's salt. In the content range of this study, the chloride binding capability of coal gangue specimens increased at first and then decreased with the increase of the molar ratios of Ca/Si and Si/Al. When the coal gangue-slag composite was added, the chloride binding capability increased with the increase of the mole ratios of Ca/Si and Si/Al, presenting a positive linear relationship.